Sensory evaluation practices - Stone, Herbert; Bleibaum, Rebecca N.; Thomas, Heather A. (Food science and technology international series., 2021)
"Sensory Evaluation Practices, Fifth Edition, presents the latest developments and methods of sensory evaluation, including those on the front end of innovation, consumer acceptance/preference, multivariate statistical analysis, discrimination testing, descriptive analysis, sensory claims substantiation for advertising, and information management. Additionally, related social psychological methods, such as laddering, design thinking, emotional profiling, and applications of qualitative and consumer co-creation and immersive techniques are explored. This book will be an ideal reference for sensory professionals, technical managers, product specialists and research directors in the food, beverage, cosmetics, and other consumer products industries of all sizes"--Publisher's description